2022
DOI: 10.1002/stc.3040
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of inertance and damping double‐skyhook control strategies for a semi‐active device combining an adjustable inerter and damper

Abstract: Summary As a classical control model, the skyhook damper configuration can be used to adapt to changes in road conditions rather than that in load conditions. Conversely, as a newly developed control model, the skyhook inerter configuration can be used to adapt to variation of load conditions but not that of road conditions. In order to solve or at least reduce the conflict between load and road adaptability, a double‐skyhook configuration that combines a skyhook inerter and a skyhook damper is proposed in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Their quarter car simulation results indicated a reduction of 28.8% in vehicle body acceleration under random road conditions. In their later work, Zhang et al (2022c) incorporated a semi-active damper to the semi-active Skyhook inerter network, realising the "semi-active double-skyhook" suspension system. Simulations under sinusoidal and random road excitations showed that these semi-active suspensions with double skyhook strategies adapt to road and vehicle loading variations, providing a more constant and comfortable ride compared to single-skyhook and passive suspensions.…”
Section: Vehicle and Seat Suspensionmentioning
confidence: 99%
“…Their quarter car simulation results indicated a reduction of 28.8% in vehicle body acceleration under random road conditions. In their later work, Zhang et al (2022c) incorporated a semi-active damper to the semi-active Skyhook inerter network, realising the "semi-active double-skyhook" suspension system. Simulations under sinusoidal and random road excitations showed that these semi-active suspensions with double skyhook strategies adapt to road and vehicle loading variations, providing a more constant and comfortable ride compared to single-skyhook and passive suspensions.…”
Section: Vehicle and Seat Suspensionmentioning
confidence: 99%